Harnessing the MinION: An example of how to establish long‐read sequencing in a laboratory using challenging plant tissue from Eucalyptus pauciflora. (5th October 2018) - Schalamun, Miriam; Nagar, Ramawatar; Kainer, David; Beavan, Eleanor; Eccles, David; Rathjen, John P.; Lanfear, Robert; Schwessinger, Benjamin
Abstract: Long‐read sequencing technologies are transforming our ability to assemble highly complex genomes. Realizing their full potential is critically reliant on extracting high‐quality, high‐molecular‐weight (HMW) DNA from the organisms of interest. This is especially the case for the portable MinION sequencer which enables all laboratories to undertake their own genome sequencing projects, due to its low entry cost and minimal spatial footprint. One challenge of the MinION is that each group has to independently establish effective protocols for using the instrument, which can be time‐consuming and costly. Here, we present a workflow and protocols that enabled us to establish MinION sequencing in our own laboratories, based on optimizing DNA extraction from a challenging plant tissue as a case study. Following the workflow illustrated, we were able to reliably and repeatedly obtain >6.5 Gb of long‐read sequencing data with a mean read length of 13 kb and an N50 of 26 kb. Our protocols are open source and can be performed in any laboratory without special equipment. We also illustrate some more elaborate workflows which can increase mean and average read lengths if this is desired. We envision that our workflow for establishing MinION sequencing, including the illustration of potential pitfalls and suggestions of how to adapt it to other tissue types, will be useful to others who plan to establish long‐read sequencing in their own laboratories.